Evaluation of the functional capacity of patients with chronic kidney disease using the ADL-Glittre test - Ramos Mariani, Henrique; Cesar Andrade, Taci Ana; Duarte Fantesia Costa Cruz, Arthur; Carvalho Dos Santos Oliveira, Paola; Christofoletti, Gustavo; Magnani Seki, Karla Luciana (O Mundo da Saúde, 2019)
Chronic diseases are becoming a serious public health problem, including chronic kidney failure (CKF), which causes significant functional losses, limitation of activities of daily living (ADL) and impairments in quality of life. As a result, the application of instruments that assess functional capacity in clinical practices becomes relevant. Thus, the objective of the present study was to evaluate the functional capacity of patients with CKF by the ADL-Glittre test. This was a cross-sectional study, including 31 male and female volunteers, divided into two groups: CKD-G (n=19) and CG (n=12), respectively. For the statistical analysis comparing categorical variables, the chi-squared test was used, and for the continuous variables the Mann-Whitney test, with a statistical significance level of 5%. There was a significant difference between the studied groups regarding the time taken to perform the ADL-Glittre [CKD-G: 3.1 (0.5) minutes and CG: 2.5 (0.2) minutes (p=0.001)] and in the ADL-Glittre reports [normal or reduced: CKD-G (0/19) and CG (6/6) (p=0.001)]. In both variables, the CKD-G obtained lower results. In conclusion, it was observed that CKD resulted in impairment of functional capacity and that the ADL-Glittre Test proved to be an appropriate instrument for the assessment of functional capacity of CKD patients.